Low-Temperature Conservation of Collection Cholera Vibrio Strains - I. V. Gracheva; A.V. Low Osin (Проблемы особо опасных инфекций, 2014)
Objective of the study is to evaluate cholera vibrio resistance to freezing and freeze preservation at -70 °C in the presence of cryoprotectors. The study outlines the results of storage of seven different V. cholerae strains within three-years term in the protective media containing glycerin or lactose (10, 20, 30 % aquatic solutions of glycerin, meat-peptone broth with 10 % of glycerin, a medium with 15 % of lactose and 3 % of gelatin) as cryoprotectors. Demonstrated is the fact that cholera vibrio death occurs during freezing-refreezing procedure and preservation of samples. After three-year conservation the numbers of living cells decrease in all types of media, but to different extent. The highest survival rate in cholera vibrios after freezing-refreezing procedure and freeze preservation in accordance with applicable protocols is observed in lactose-gelatin medium. When using aquatic solution of glycerin as protective medium, optimum turns out to be the cryoprotector concentration equal to 20 %. After three-year preservation at -70 °C all the strains, irrespective of the protective medium composition, retain their basic diagnostically significant phenotypic characteristics. Thus, cholera vibrios can be conserved free from subcultures within three-year term (period of observation) without alterations to their basic diagnostic properties in all tested protective media but at -70 °C.